Anti-bacterial efficacy of Aloe vera against E. Faecalis in comparison to other intracanal medicaments: A systematic review and meta-analysis - Rabia Tariq; Zohaib Khurshid; Waqas Ahmed Farooqui; Nejdet Adanir (Elsevier, 2023)
Introduction: This review article aims to evaluate the antibacterial efficacy of Aloe vera against Enterococcus faecalis (E. faecalis) in comparison to other intracanal medicaments by assessing experimental in-vitro studies associated with the objective, many of which performed bacterial inoculation on extracted human teeth or directly on laboratory petri dishes. Materials & Methods: Publications from 2012 to 2022 were retrieved from databases, including PubMed, Scopus, and Cochrane Library, and they were screened against our inclusion criteria, leading to the incorporation of 18 studies into the systematic review and nine into the meta-analysis. Colony-forming units (CFUs) in the Aloe vera group were compared with saline, sodium hypochlorite (NaOCl), chlorhexidine (CHX), and calcium hydroxide (CaOH) using a meta-analysis (Stata software version 16.0), and forest plots were computed to record the sample size, mean and standard deviation value of the outcome CFU, and 95% confidence intervals. Results: This systematic review indicates that Aloe vera demonstrates bactericidal properties that are higher than or similar to those of saline and CaOH, but CHX, NaOCl, and propolis exhibited higher antibacterial properties against E. faecalis than Aloe vera. In a meta-analysis, Aloe vera showed a non-significantly lower CFU count than CaOH and saline (p > 0.05), while Aloe vera had a higher CFU count than CHX and NaOCl (p > 0.05). Conclusion: In summary, Aloe vera exhibits antibacterial capabilities against E. faecalis that are superior or equal to those of saline and CaOH, respectively, while CHX and NaOCl showed greater antibacterial efficacy against E. faecalis than Aloe vera (PROSPERO registration no. CRD42022314790).